A Custom-Made, Low-Cost Intraoperative Fluorescence Navigation System with Indocyanine Green for Sentinel Lymph Node Biopsy in Skin Cancer - Fujisawa, Yasuhiro; Nakamura, Yasuhiro; Kawachi, Yasuhiro; Otsuka, Fujio (Dermatology, 2011)
Background: Recently, indocyanine green (ICG) fluorescence imaging has been reported as new method to detect sentinel lymph nodes (SLNs). However, high introduction costs limit its use. Objective: The purpose of this study was to test an ICG fluorescence detection system constructed with parts commonly available on the market and to compare the SLN detection rate with that of the conventional combined dye and RI methods. Methods: We constructed this system using a charge-coupled device camera and light-emitting diodes. Results: We could construct our system at a cost of less than USD 1,600. This system could trace lymphatic channels through the skin and detect SLNs in 16 patients with skin cancer. However, SLNs in the neck were difficult to detect through the skin. Conclusion: Our system could be assembled at a reasonable cost and allowed us to detect SLNs efficiently. It may be used as an alternative to radiotracer for detecting SLNs located in the groin and axillary regions.